The Role of Immunotherapy in Non-transplant Eligible Multiple Myeloma - Bobin, Arthur; Gardeney, Hélène; Sabirou, Florence; Gruchet, Cécile; Lévy, Anthony; Nsiala, Laly; Cailly, Laura; Tomowiak, Cécile; Torregrosa, Jose; Guidez, Stéphanie; Leleu, Xavier (Frontiers in Oncology, 2020)
As the global population is aging and survival in multiple myeloma (MM) is increasing, treating older MM patients, redefined as non-transplant eligible (NTE), is becoming more frequent. Yet, treating these patients remains a real challenge especially because of a marked heterogeneity in the population and an increased susceptibility to treatment toxicity. Indeed, the balance between efficacy and safety must be considered at all time throughout the treatment history for these patients. Therefore, younger and older patients were historically treated in a very different way, even though the safety profile of most anti-myeloma drugs has drastically improved over the years. The emergence of immunotherapy (IT) has largely widened the therapeutic options available in MM and above all has allowed a therapy at optimal dose, and therefore optimal activity, for all patients independently of their frailty features, with no increase in safety issues. Among the novel anti-myeloma IT-based agents, anti-CD38 monoclonal antibodies (mAbs) are now becoming the new backbone of treatment for NTE patients, in association with lenalidomide and dexamethasone. Moreover, several new IT-based drugs are currently being developed and investigated either alone or in association; such as new anti-CD38 mAbs, anti-CD38 mAbs with many different combinations, but also the CAR-T cells, bispecific T-cell engager (BiTEs), or antibody drug conjugate (ADC) targeting BCMA. One would expect that immunotherapy will ultimately change and even transform the MM landscape, even for elderly patients. Immunotherapy represents a shift in treatment paradigm in MM as it provides truly efficient drugs with a very favorable safety profile.